2007
DOI: 10.1029/2006gl028783
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic conjugate observation of the F3 layer using the SEALION ionosonde network

Abstract: Results from the meridional ionosonde network located in Southeast Asia (SEALION) demonstrate the interesting nature of the F3 layer, showing its generation mechanism. Ionograms obtained on 16 November 2004 and 31 March 2005 at Chiang Mai (CMU; geographic latitude 18.8°N, geographic longitude 98.9°E, and magnetic latitude 13.2°N), Chumphon (CPN; 10.7°N, 99.4°E, and 3.2°N) and Kototabang (KTB; 0.2°S, 100.3°E, and 10.1°S) showed significant differences between CPN near the magnetic equator, and CMU and KTB in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…This mechanism adequately explains the high occurrence of the F 3 layer observations at Fortaleza, Kwajalein, and Vanimo in summer, and the low occurrence at Jicamarca. Similar observational results were also obtained at other magnetic equatorial stations [Jenkins et al, 1997;Rama Rao et al, 2005;Uemoto et al, 2007].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This mechanism adequately explains the high occurrence of the F 3 layer observations at Fortaleza, Kwajalein, and Vanimo in summer, and the low occurrence at Jicamarca. Similar observational results were also obtained at other magnetic equatorial stations [Jenkins et al, 1997;Rama Rao et al, 2005;Uemoto et al, 2007].…”
Section: Discussionsupporting
confidence: 78%
“…This additional layer was later renamed the F 3 layer because it has the same chemical composition as the F region . After that, the subject of the F 3 layer received extensive investigations at low and equatorial latitudes concerning its spatial and temporal distribution [Jenkins et al, 1997;Balan et al, 1998;Hsiao et al, 2001;Batista et al, 2002;Rama Rao et al, 2005;Zain et al, 2008;Uemoto et al, 2007;Sreeja et al, 2010;Zhao et al, 2011], and also its storm time characteristics [Zhao et al, 2005;Paznukhov et al, 2007;Balan et al, 2008;Sreeja et al, 2009;Zong et al, 2010]. The mechanism of the storm time F 3 layer resembles that in quiet periods and was caused by a rapid upward E × B drift resulting from an eastward penetration electric field but sometimes can be caused by strong field-aligned diffusion due to the storm time meridional wind surges as proposed by Lin et al [2009aLin et al [ , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the F2 layer stratification occurred over a narrow region between the magnetic equator and the peak of the southern equatorial anomaly, a result which corroborates with Jenkins et al (1997). The first simultaneous observation of the F3 layer on either side of the geomagnetic equator was reported by Uemoto et al (2007). Rama Rao et al (2005) reported the ionosonde observations of the F3 layer over Waltair (17.7 • N; 83.3 • E; dip lat ∼ 8.2 • N) in India.…”
Section: Introductionsupporting
confidence: 64%
“…It is obvious that the equatorial F2 layer stratification and the occurrence of an additional layer in the equatorial ionosphere is the one phenomenon. [32], the subject of the F3 layer received extensive investigations at low and equatorial latitudes concerning its spatial and temporal distribution based on the ionosonde observations of single or several stations distributed at three longitudinal sectors (American, Indian, and Pacific longitudes) [34][35][36][37][38][39][40][41][42][43][44]. From these investigations, it is known that the F3 layer can be observed under geomagnetically quiet conditions.…”
Section: Progress Of the Recent Study On The Stratification Of The F2mentioning
confidence: 99%